PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS VIII - Dua Lina, Oliva; Nong Bunga, Yohanes; Hadi Jaya Putra, Sukarman (Jurnal Biogenerasi, 2024)
Science is one of the subjects in the independent curriculum, including at the junior high school level. Science is directly related to human life and studies everything that lives in the world. Science learning is delightful, but learning that is only centered on teachers sometimes feels unpleasant and boring. This study aims to analyze the validation and feasibility of LKPD based on the problem-based learning (PBL) model on the human digestive system material for grade VII junior high school. This research was conducted at St. Mikhael Brai Catholic Junior High School, Alok Timur District, Sikka Regency. The research method used is development or Research and Development with a 4-D model. Development steps: needs analysis, product design, expert validation, small class trials, and product revisions. Data were collected through observations involving teachers and students. The results of the study showed that the LKPD developed obtained perfect validation, with an average score of 100%, so the LKPD product developed was very feasible to be used as a learning medium.